2019
DOI: 10.1016/j.redox.2019.101285
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training prevents the perivascular adipose tissue-induced aortic dysfunction with metabolic syndrome

Abstract: The aim of the study was to determine the effects of exercise training on improving the thoracic perivascular adipose tissue (tPVAT) phenotype (inflammation, oxidative stress, and proteasome function) in metabolic syndrome and its subsequent actions on aortic function. Methods Lean and obese (model of metabolic syndrome) Zucker rats (n=8/group) underwent 8-weeks of control conditions or treadmill exercise (70% of max speed, 1 h/day, 5 days/week). At the end of the intervention, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 72 publications
2
37
0
Order By: Relevance
“…Consistent with the current study, researchers have speculated that local factors other than endovascular shear stress could contribute to arterial function 36,37 . The impaired function of arteries in obesity were partly due to metabolic syndrome of PVAT, 22 and the functionality rather than total amount of AT are more crucial for cardiometabolic risk 38 . Among several potential candidates of ADRF, H 2 S synthesized by CSE in PVAT has been suggested as an important vasodilator; 25 down‐regulation of PVAT derived H 2 S in long‐term obesity could be critically responsible for vascular dysfunction 38 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Consistent with the current study, researchers have speculated that local factors other than endovascular shear stress could contribute to arterial function 36,37 . The impaired function of arteries in obesity were partly due to metabolic syndrome of PVAT, 22 and the functionality rather than total amount of AT are more crucial for cardiometabolic risk 38 . Among several potential candidates of ADRF, H 2 S synthesized by CSE in PVAT has been suggested as an important vasodilator; 25 down‐regulation of PVAT derived H 2 S in long‐term obesity could be critically responsible for vascular dysfunction 38 .…”
Section: Discussionsupporting
confidence: 85%
“…We observed a significant difference in vascular reactivity to 5‐HT between mesenteric arteries with and without PVAT, and vascular function in high‐fat diet rats seemed to be reversed after exercise intervention. Studies have shown that exercise training was effective on regulating metabolic syndrome of PVAT around thoracic aorta from obese animals 22 and subsequently normalizing arterial relaxation 20,21,23 . The independent role of PVAT on the mesenteric artery after long‐term aerobic exercise was further validated by transferring PVAT from each group to an untreated artery for evaluation of vascular contraction.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of exercise to influence endothelial transport of insulin and glucose [44] and to mediate enhanced insulin-stimulated blood flow via both the nutritive and non-nutritive routes [88] is likely to be particularly important for the prevention of type 2 diabetes. Finally, emerging data from rodents indicate that exercise also positively impacts endothelial function and vascular biology in adipose depots [95] and is likely to play a role in other key organs, such as the brain, liver and pancreas.…”
Section: Muscle-centric Vs Integrative View Of the Impact Of Exercisementioning
confidence: 99%
“…Compared with lean PVAT, obese PVAT secretes more pro-inflammatory adipokines, including TNFα, leptin, IL-6, plasminogen activator, and resistin, which switch PVAT into a pro-inflammatory and pro-oxidative phenotype that promotes atherosclerotic plaque formation and instability, not only in coronary arteries but also in other blood vessels [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. In addition, PVAT dysfunction has been related with the deregulation of blood vessels contractility, so the inflammation and oxidative stress abolish PVAT’s natural protective anti-contractile effect, contributing to the development of hypertension [ 35 , 36 , 37 ].…”
Section: Adipose Tissue Dysfunction and Cvdsmentioning
confidence: 99%